The Prominent Deck B Phenomenon in Schizophrenia: An Empirical Study on Iowa Gambling Task - Xu, Mei; Lee, We-Kang; Ko, Chih-Hung; Chiu, Yao-Chu; Lin, Ching-Hung (Frontiers in Psychology, 2021)
Background: Iowa gambling task (IGT) was established to evaluate emotion-based decision-making ability under uncertain circumstances in clinical populations, including schizophrenia (Sz). However, there remains a lack of stable behavioral measures regarding discrimination for decision-making performance in IGT between schizophrenic cases and healthy participants. None of the Sz-IGT studies specifically verify the prominent deck B (PDB) phenomenon gradually revealed in other populations. Here we provided a global review and empirical study to verify the Sz-IGT issues. Methods: In efforts to seek reliable and valid behavioral measures, we reviewed 38 studies using IGT to investigate decision-making behavior in Sz groups, and also, the IGT, Wisconsin Card Sorting Test (WCST) and clinical symptoms evaluations were administered to 61 schizophrenia or schizoaffective cases diagnosed by psychiatrists and 62 demographically-matched healthy participants. Results: There were no valid behavioral measures in IGT to significantly identify the decision-making dysfunction of Sz, but Sz cases, on average, made more choices from disadvantageous deck B relative to other decks, particularly in the later learning process (block 3-5). Compared to the control group, Sz was more impaired in WCST. High-frequent gain decks B and D showed significant correlations with WCST, but no correlations between clinical symptoms and IGT/WCST. Conclusions: Gain-loss frequency imposes a dominant and stable impact on decision-making processing in Sz and control groups. PDB phenomenon is essentially challenging to be observed on the ground of the expected value viewpoint approach in IGT in both populations. Consequently, it should be cautious when launching the IGT to assess the decision-making ability of Sz under a clinical scenario.